Perumusan Isu Strategis Kebijakan Investasi pada Sektor Pariwisata di Indonesia Berbasis Berita Media Online - Raditya, Raditya (Multiverse: Open Multidisciplinary Journal, 2023)
As a primary sector in supporting the economic growth, the tourism sector relies on investments to escalate the multiplier-effect. However, the utilization of potential resources in the tourism sector is not at the optimal level. Therefore, it is necessary for the government to recognize strategic issues in the tourism investment sector for formulating the appropriate policy. By utilizing the Latent Dirichlet Allocation (LDA) and the Text Network Analysis (TNA) methods, this study tries to extract strategic issues of the tourism investment sector from public discourses on the online media news. The results indicate that strategic issues in the tourism investment sector consist of three aspects, namely actor, action, and factor. The actor is the crucial aspect amongst others for its complexity.